Improving Educational Quality Through Curriculum Development: An Empirical Investigation Using Stakeholder Feedback Data. Issue 2 (April 2019) - Islam, Amirul
Using feedback data from stakeholders, the study examines several aspects of the curriculum offered by a program offering entity (POE) in Bangladesh. Analysis of the data shows that the opinions of the stakeholders from various groups resonate together for evaluation areas like need assessment, curriculum mapping, and feedback mechanism. However, opinions expressed by students, both current and alumni, diverge from the opinions expressed by the academic community on matters like "program load." The qualitative analysis of the text data obtained through some open-ended questions reveals that the respondents support an academic environment free from campus politics and incorporation of more courses related to Information Communication Technology (ICT) for curriculum development.